Silicon-carbon composite negative electrode material coated with heterojunction structure on surface and preparation method of silicon-carbon composite negative electrode material
By covering the surface of the silicon-carbon composite particles with titanium oxide and titanium nitride layers to form a heterojunction structure, the problem of capacity attenuation and poor rate performance caused by volume expansion of silicon particles during lithium embedding is solved, and high specific capacity and good cycle performance are achieved.
Patent Information
- Application Number
- CN202411907587.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-23
- Publication Date
- 2025-03-28
AI Technical Summary
The volume expansion of existing silicon particles during lithium embedding leads to the problems of fast capacity decay and poor rate performance during circulation.
The titanium oxide layer and the titanium nitride layer are coated by atomic layer deposition method on the surface of silicon-carbon composite particles to form a heterojunction structure, and the cyclic stability and rate performance of the material are enhanced by annealing treatment.
The high specific capacity and good circulation performance of silicon-carbon composite anode material were achieved, with the first efficiency reaching 90-95%, and the capacity retention rate was still as high as 92% after 100 weeks of circulation.
Smart Images

Figure CN119725456A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of silicon-carbon negative electrode materials, and in particular to a silicon-carbon composite negative electrode material with a surface coated with a heterojunction structure and a preparation method thereof. Background Art
[0002] With the vigorous development of the new energy industry, the industrialization of diversified negative electrode materials is accelerating. At present, the specific energy of graphite negative electrode materials is not enough to support electric vehicles in long-distance transportation, so the development of high-specific-energy negative electrode materials has emerged. Silicon particles with lithium insertion have a theoretical specific capacity of up to 4200mAh / g and are highly favored. However, due to the expansion of silicon elements during the lithium insertion process (>300%), this volume change will cause the silicon particles to continue to crack and break with the continuous lithium insertion, and continue to consume electrolyte and Li + , which reduces the material's cycle stability and causes severe voltage decay. Therefore, silicon materials are doped with carbon materials to form composite materials.
[0003] Atomic layer deposition (ALD) technology has broad application potential in the field of electronic materials due to its high controllability of deposition thickness, composition and structure, and its excellent deposition uniformity and consistency.
[0004] KIM et al. coated SiO2 with TiO2. The material had a first charge capacity of 1265 mAh / g as a negative electrode, but the first coulombic efficiency was only 72%. LI et al. obtained SiO2 with a watermelon-like structure by ball milling. x The highly dispersed conductive TiO2 nanoparticles inside the @TiO2 composite material and the outer carbon shell jointly promote the electron and Li + The rapid transport enhances the electrode reaction kinetics, but the volume changes greatly, and long-term cycling is not conducive to the structural integrity of the active particles. After 100 cycles at a current density of 100 mA / g, there is still a reversible specific capacity of 804 mAh / g.
[0005] Therefore, how to obtain a silicon-carbon composite negative electrode material with high specific capacity and good cycle performance and a preparation method thereof is a technical problem that needs to be solved at present. Summary of the invention
[0006] The purpose of the present invention is to provide a silicon-carbon composite negative electrode material with a surface-coated heterojunction structure and a preparation method thereof, so as to solve the technical problems of rapid capacity decay and poor rate performance during the cycle caused by the expansion of existing silicon particles.
[0007] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:
[0008] The present invention provides a method for preparing a silicon-carbon composite negative electrode material having a surface-coated heterojunction structure, comprising the following steps:
[0009] S1. A titanium oxide layer is coated on the surface of the silicon-carbon composite particles by atomic layer deposition to obtain silicon-carbon composite particles coated with titanium oxide layer;
[0010] S2. A titanium nitride layer is coated on the surface of the silicon-carbon composite particles coated with the titanium oxide layer by atomic layer deposition;
[0011] S3. Annealing the material deposited in step S2 to obtain a silicon-carbon composite negative electrode material with a surface-coated heterojunction structure.
[0012] Furthermore, in step S1 and step S2, the atomic layer deposition method includes the following steps:
[0013] a. Load the reactant particles onto the reaction chamber carrier, evacuate the reaction chamber, and pass inert gas;
[0014] b. Using an inert gas as a carrier gas, the reaction precursor is added into the reaction chamber in a pulsed manner for deposition;
[0015] c. After the deposition is completed, the reaction chamber is evacuated by passing inert gas;
[0016] d. Using an inert gas as a carrier gas, an oxidation precursor or a nitridation precursor is added into the reaction chamber in a pulsed manner to perform oxidation or nitridation treatment;
[0017] e. Repeat steps b to d, with the number of cycles ≥ 1;
[0018] The reactant particles are silicon-carbon composite particles or silicon-carbon composite particles coated with a titanium oxide layer.
[0019] Furthermore, in the step S1, in the atomic layer deposition method, the oxidation precursor includes one or more of water vapor, oxygen and ozone;
[0020] In the step S2, in the atomic layer deposition method, the nitridation precursor includes ammonia and / or nitrogen.
[0021] Furthermore, in the step S1 and step S2, in the atomic layer deposition method, in b, the reaction precursors independently include one or more of Ti(OC2H5)4, TiCl4, TiI4, TiCl4 and Ti(OCH(CH3)2)4.
[0022] Furthermore, in the step S1 and step S2, in the atomic layer deposition method, in the step b, the flow rate of the carrier gas is 15 to 25 sccm, and the residence time of the reaction precursor in the reaction chamber is 5 to 20 s.
[0023] Furthermore, in the atomic layer deposition method in step S1 and step S2, in step b, the deposition temperature is 150-400° C., the pressure in the reaction chamber is 200-400 mTorr, and the pulse time is 300-800 ms.
[0024] Furthermore, in the step S1 and step S2, in the atomic layer deposition method, in the d, the pulse time is 400 to 850 ms, the flow rate of the carrier gas is 15 to 25 sccm, and the residence time of the oxidation precursor or the nitridation precursor in the reaction chamber is 15 to 60 s.
[0025] Further, the inert gas independently contains nitrogen and / or argon, and the temperature of the oxidation or nitridation treatment is 150-200° C.;
[0026] The annealing temperature is 300-500° C., and the annealing time is 2-5 hours.
[0027] Furthermore, the thickness of the titanium oxide layer is 0.5-10 nm, and the thickness of the titanium nitride layer is 0.5-10 nm.
[0028] The present invention provides a silicon-carbon composite negative electrode material with a surface-coated heterojunction structure, comprising silicon-carbon composite particles and a titanium oxide layer coated on the surface of the silicon-carbon composite particles, and a titanium nitride layer coated on the titanium oxide layer;
[0029] The silicon-carbon composite particles have a C content of 10-90%, a Si content of 10-90%, and a particle size of 8-15 μm.
[0030] Beneficial effects of the present invention:
[0031] (1) The composite material of the present invention uses an atomic layer deposition method during the preparation process to deposit titanium oxide and titanium nitride on the porous silicon-carbon composite skeleton.
[0032] (2) TiO2 and TiN have high redox potentials, are not easily oxidized, and have a bandgap of >3.0 eV, which makes them exhibit advantages such as high melting point, high hardness, high thermal conductivity, and chemical stability. Since the work function of titanium nitride is smaller than that of titanium oxide, when the two come into contact to form a heterojunction, the electrons on the TiN side will spontaneously transfer to TiO2, establishing charge redistribution at the heterojunction. In addition, TiO2 / TiN has an anchoring effect on silicon particles, effectively alleviating their volume expansion, providing a stable electronic conductive network structure, improving the material's cycle stability, and improving rate performance.
[0033] (3) The capacity of the battery prepared by the negative electrode material coated with titanium oxide and titanium nitride structure of the present invention reaches 1900-2300 mAh / g, the initial efficiency reaches 90-95%, and the capacity retention rate is still as high as 92% after 100 cycles. BRIEF DESCRIPTION OF THE DRAWINGS
[0034] Figure 1 This is a process flow chart for preparing a silicon-carbon composite negative electrode material according to the present invention;
[0035] Figure 2 This is a schematic diagram of the heterojunction structure composed of titanium nitride and titanium oxide in the silicon-carbon composite negative electrode material prepared by the present invention. DETAILED DESCRIPTION
[0036] The present invention provides a method for preparing a silicon-carbon composite negative electrode material having a surface-coated heterojunction structure, comprising the following steps:
[0037] S1. A titanium oxide layer is coated on the surface of the silicon-carbon composite particles by atomic layer deposition to obtain silicon-carbon composite particles coated with titanium oxide layer;
[0038] S2. A titanium nitride layer is coated on the surface of the silicon-carbon composite particles coated with the titanium oxide layer by atomic layer deposition;
[0039] S3. Annealing the material deposited in step S2 to obtain a silicon-carbon composite negative electrode material with a surface-coated heterojunction structure.
[0040] In the present invention, in step S1 and step S2, the atomic layer deposition method includes the following steps:
[0041] a. Load the reactant particles onto the reaction chamber carrier, evacuate the reaction chamber, and pass inert gas;
[0042] b. Using an inert gas as a carrier gas, the reaction precursor is added into the reaction chamber in a pulsed manner for deposition;
[0043] c. After the deposition is completed, the reaction chamber is evacuated by passing inert gas;
[0044] d. Using an inert gas as a carrier gas, an oxidation precursor or a nitridation precursor is added into the reaction chamber in a pulsed manner to perform oxidation or nitridation treatment;
[0045] e. Repeat steps b to d, with the number of cycles ≥ 1;
[0046] The reactant particles are silicon-carbon composite particles or silicon-carbon composite particles coated with a titanium oxide layer.
[0047] In the present invention, in step S1, in the atomic layer deposition method, the oxidation precursor comprises one or more of water vapor, oxygen and ozone, preferably oxygen;
[0048] In the step S2, in the atomic layer deposition method, the nitridation precursor includes ammonia and / or nitrogen, preferably ammonia.
[0049] In the present invention, in the step S1 and step S2, in the atomic layer deposition method, in the b, the reaction precursors independently include one or more of Ti(OC2H5)4, TiCl4, TiI4, TiCl4 and Ti(OCH(CH3)2)4, preferably one or more of Ti(OC2H5)4, TiCl4 and Ti(OCH(CH3)2)4.
[0050] In the present invention, in the step S1 and step S2, in the atomic layer deposition method, in b, the flow rate of the carrier gas is 15 to 25 sccm, preferably 18 to 22 sccm, and more preferably 20 sccm; the residence time of the reaction precursor in the reaction chamber is 5 to 20 s, preferably 10 to 15 s, and more preferably 12 s.
[0051] In the present invention, in the step S1 and step S2, in the atomic layer deposition method, in the step b, the deposition temperature is 150-400°C, preferably 200-350°C, and more preferably 250-300°C; the pressure in the reaction chamber is 200-400mTorr, preferably 250-350mTorr, and more preferably 300mTorr; the pulse time is 300-800ms, preferably 400-700ms, and more preferably 500-600ms.
[0052] In the present invention, in the step S1 and step S2, in the atomic layer deposition method, in the d, the pulse time is 400 to 850 ms, preferably 500 to 800 ms, and more preferably 600 to 700 ms; the flow rate of the carrier gas is 15 to 25 sccm, preferably 18 to 22 sccm, and more preferably 20 sccm; the residence time of the oxidation precursor or the nitride precursor in the reaction chamber is 15 to 60 s, preferably 20 to 50 s, and more preferably 30 to 40 s.
[0053] In the present invention, the inert gas independently comprises nitrogen and / or argon, preferably nitrogen; the temperature of the oxidation or nitridation treatment is 150-200°C, preferably 180°C.
[0054] In the present invention, the annealing temperature is 300-500° C., preferably 350-450° C., and more preferably 400° C.; the annealing time is 2-5 hours, and preferably 4 hours.
[0055] In the present invention, the thickness of the titanium oxide layer is 0.5 to 10 nm, preferably 0.5 to 5 nm, and more preferably 1 to 3 nm; the thickness of the titanium nitride layer is 0.5 to 10 nm, preferably 0.5 to 5 nm, and more preferably 1 to 3 nm.
[0056] The present invention provides a silicon-carbon composite negative electrode material with a surface-coated heterojunction structure, comprising silicon-carbon composite particles and a titanium oxide layer coated on the surface of the silicon-carbon composite particles, and a titanium nitride layer coated on the titanium oxide layer;
[0057] The silicon-carbon composite particles have a C content of 10-90%, a Si content of 10-90%, and a particle size of 8-15 μm.
[0058] In the present invention, the C content in the silicon-carbon composite particles is preferably 20-80%, more preferably 30-70%; the Si content is preferably 20-80%, more preferably 30-70%; and the particle size of the silicon-carbon composite particles is preferably 10 μm.
[0059] The present invention establishes a new silicon-carbon composite negative electrode material based on the original CN 117457873 A, establishes a TiO2 / TiN heterojunction on the particle surface, forms a built-in electric field, promotes carrier transfer and separation at the contact interface, and further improves the intrinsic ion and electronic conductivity of the composite material.
[0060] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.
[0061] Example 1
[0062] The silicon-carbon composite negative electrode material with a surface-coated heterojunction structure described in this embodiment includes silicon-carbon composite particles and a TiO2 / TiN layer coated on the surface of the silicon-carbon composite particles; the Si:C in the silicon-carbon composite particles is 1:5; the product derived from Example 4 in CN117457873A has an average particle size of 10μm, and the thickness of the titanium oxide and titanium nitride layers are both 0.83nm.
[0063] The specific steps are as follows:
[0064] S1. A titanium oxide layer is obtained on the surface of the silicon-carbon composite particles by an atomic layer deposition method to obtain silicon-carbon composite particles coated with the titanium oxide layer, specifically:
[0065] (1) loading silicon-carbon composite particles onto a reaction chamber carrier of an atomic layer deposition device, evacuating the reaction chamber, and passing an inert gas;
[0066] (2) The deposition temperature was set to 220°C and the pressure in the reaction chamber was set to 300 mTorr;
[0067] (3) The precursor bottle source is Ti(OCH2CH3)5 loaded with nitrogen and added into the reaction chamber in a pulsed manner for 400 ms with a carrier gas flow rate of 20 sccm. The residence time of the precursor in the reaction chamber is 15 s.
[0068] (4) Cleaning the reaction chamber with nitrogen gas and evacuating the chamber;
[0069] (5) nitrogen-loaded oxygen was added to the reaction chamber in a pulsed manner, the pulse time was set to 600 ms, the carrier gas flow rate was 20 sccm, and the residence time of the oxygen in the reaction chamber was 20 s;
[0070] (6) Repeat steps (3) to (5) until the titanium source is deposited once, which is called a deposition cycle. The number of deposition cycles is 5.
[0071] S2. Coating a titanium nitride layer on the surface of the silicon-carbon composite particles coated with the titanium oxide layer to obtain the silicon-carbon composite negative electrode material, specifically:
[0072] (1) loading the composite particles onto a reaction chamber carrier of an atomic layer deposition device, evacuating the reaction chamber and passing nitrogen gas;
[0073] (2) The deposition temperature was set to 150°C and the pressure in the reaction chamber was set to 200 mTorr;
[0074] (3) using argon gas to load the reaction oxidation precursor TiCl4 into the reaction chamber in a pulsed manner, the time is 500ms, the carrier gas flow rate is 25sccm, and the residence time of the reaction precursor in the reaction chamber is 20s;
[0075] (4) Cleaning the reaction chamber with argon gas and evacuating the chamber;
[0076] (5) nitrogen gas loaded with argon gas was added into the reaction chamber in a pulsed manner, the pulse time was set to 650 ms, the carrier gas flow rate was 25 sccm, and the residence time of the nitridation precursor in the reaction chamber was 50 s;
[0077] (6) Repeat steps (3) to (5), wherein one nitrogen source deposition is one deposition cycle, and the deposition cycles are 5 times in total.
[0078] Finally, the deposited material was annealed at 400°C for 3h to obtain coated silicon-carbon composite particles denoted as (C / Si)@1TiO2 / TiN.
[0079] Example 2
[0080] The difference between the silicon-carbon composite negative electrode described in this embodiment and that in embodiment 1 is that the thickness of the titanium oxide and titanium nitride layers is different, and the deposition thickness of this embodiment is about 1.42 nm. Titanium oxide is deposited 10 times and titanium nitride is deposited 10 times, for a total of 20 times, and the resulting composite silicon-carbon negative electrode material is recorded as (C / Si)@2TiO2 / TiN.
[0081] Example 3
[0082] The difference between the silicon-carbon composite negative electrode described in this embodiment and that in embodiment 1 is that the thickness of titanium oxide and titanium nitride is different, and the deposition thickness of this embodiment is about 2.50 nm. The deposition of titanium oxide and titanium nitride is 15 times, 30 times in total, and the obtained composite silicon-carbon negative electrode material is recorded as C / Si@3TiO2 / TiN.
[0083] Example 4
[0084] The difference between the silicon-carbon composite negative electrode described in this embodiment and that in embodiment 1 is that the thickness of titanium oxide and titanium nitride is different, and the deposition thickness in this embodiment is about 3.46 nm. The number of times of deposition of titanium oxide and titanium nitride is 20 times respectively, for a total of 40 times, and the obtained composite silicon-carbon negative electrode material is recorded as C / Si@4TiO2 / TiN.
[0085] Example 5
[0086] The difference between the silicon-carbon composite negative electrode described in this embodiment and that in embodiment 1 is that the thickness of titanium oxide and titanium nitride is different, and the deposition thickness in this embodiment is about 4.20 nm. The number of times of deposition of titanium oxide and titanium nitride is 25 times, a total of 50 times, and the obtained composite silicon-carbon negative electrode material is recorded as C / Si@5TiO2 / TiN.
[0087] Example 6
[0088] The difference between the silicon-carbon composite negative electrode described in this embodiment and that in Embodiment 1 is that the thickness of titanium oxide is different. The deposition thickness in this embodiment is about 2.73 nm.
[0089] S1. A titanium oxide layer is obtained on the surface of the silicon-carbon composite particles by an atomic layer deposition method to obtain silicon-carbon composite particles coated with a (C / Si)@TiO2 titanium oxide layer, specifically:
[0090] The silicon-carbon composite particles are loaded on a reaction chamber carrier of an atomic layer deposition device, and the reaction chamber is evacuated and nitrogen is passed through;
[0091] (2) Set the deposition temperature to 220°C and the pressure in the reaction chamber to 250 mTorr;
[0092] (3) nitrogen-loaded oxidation precursor Ti(OCH(CH3)2)4 was added into the reaction chamber in a pulsed manner for 400 ms with a carrier gas flow rate of 15 sccm. The residence time of the reaction precursor in the reaction chamber was 12 s.
[0093] (4) Cleaning the reaction chamber with nitrogen and evacuating the chamber;
[0094] (5) using argon gas as a carrier to add the oxidation precursor ozone into the reaction chamber in a pulsed manner, setting the pulse time to 400 ms, the carrier gas flow rate to 22 sccm, and the residence time of the oxidation precursor in the reaction chamber to 15 s;
[0095] (6) Repeat steps (3) to (5) by changing the type of reaction precursor until the titanium source is deposited once, which is considered one deposition cycle. The number of deposition cycles is 17.
[0096] S2. The silicon-carbon composite particles coated with the titanium oxide layer are coated with a titanium nitride layer to obtain the silicon-carbon composite negative electrode material, specifically:
[0097] The silicon-carbon composite particles are loaded on a reaction chamber carrier of an atomic layer deposition device, and the reaction chamber is evacuated and nitrogen is passed through;
[0098] (2) Set the deposition temperature to 220°C and the pressure in the reaction chamber to 250 mTorr;
[0099] (3) nitrogen-loaded oxidation precursor TiCl4 was added into the reaction chamber in a pulsed manner for 400 ms, with a carrier gas flow rate of 15 sccm, and the residence time of the reaction precursor in the reaction chamber was 12 s;
[0100] (4) Cleaning the reaction chamber with nitrogen and evacuating the chamber;
[0101] (5) The oxidation precursor ammonia gas is loaded with argon gas and added into the reaction chamber in a pulsed manner, the pulse time is set to 400 ms, the carrier gas flow rate is 22 sccm, and the residence time of the oxidation precursor in the reaction chamber is 15 s.
[0102] (6) Repeat steps (3) to (5) until the nitrogen source is deposited once, which is called one deposition cycle. The number of deposition cycles is 17 times, and the total number of deposition cycles is 34.
[0103] Finally, the deposited material was annealed at 500°C for 3h, and the obtained composite silicon-carbon negative electrode material was recorded as (C / Si)@6TiO2 / TiN.
[0104] Example 7
[0105] The difference between the silicon-carbon composite negative electrode described in this embodiment and that in Embodiment 1 is that the thicknesses of titanium oxide and titanium nitride are different. The deposition thickness in this embodiment is about 2.74 nm.
[0106] S1. A titanium oxide layer is obtained on the surface of the silicon-carbon composite particles by an atomic layer deposition method to obtain silicon-carbon composite particles coated with the titanium oxide layer, specifically:
[0107] The silicon-carbon composite particles are loaded on a reaction chamber carrier of an atomic layer deposition device, and the reaction chamber is evacuated and passed with an inert gas;
[0108] (2) Set the deposition temperature to 280°C and the pressure in the reaction chamber to 350 mTorr;
[0109] (3) nitrogen-loaded reaction precursor TiCl5 was added into the reaction chamber in a pulsed manner for 400 ms, with a carrier gas flow rate of 15 sccm, and the residence time of the reaction precursor in the reaction chamber was 30 s;
[0110] (4) Cleaning the reaction chamber with nitrogen and evacuating the chamber;
[0111] (5) using argon gas to carry the oxidation precursor ozone and add it into the reaction chamber in a pulsed manner, setting the pulse time to 400 ms, the carrier gas flow rate to 22 sccm, and the residence time of the oxidation precursor in the reaction chamber to 25 s;
[0112] (6) Repeat steps (3) to (5) until the titanium source is deposited once, which is called one deposition cycle. The number of deposition cycles is 17.
[0113] S2. The silicon-carbon composite particles coated with the titanium oxide layer are coated with a titanium nitride layer to obtain the silicon-carbon composite negative electrode material, specifically:
[0114] The silicon-carbon composite particles are loaded on a reaction chamber carrier of an atomic layer deposition device, and the reaction chamber is evacuated and nitrogen is passed through;
[0115] (2) Set the deposition temperature to 220°C and the pressure in the reaction chamber to 250 mTorr;
[0116] (3) nitrogen-loaded oxidation precursor TiCl4 was added into the reaction chamber in a pulsed manner for 400 ms, with a carrier gas flow rate of 15 sccm, and the residence time of the reaction precursor in the reaction chamber was 12 s;
[0117] (4) Cleaning the reaction chamber with nitrogen and evacuating the chamber;
[0118] (5) The oxidation precursor ammonia gas is loaded with argon gas and added into the reaction chamber in a pulsed manner, the pulse time is set to 400 ms, the carrier gas flow rate is 22 sccm, and the residence time of the oxidation precursor in the reaction chamber is 15 s.
[0119] (6) Repeat steps (3) to (5) until the nitrogen source is deposited once, which is called one deposition cycle. The number of deposition cycles is 17 times, and the total number of deposition cycles is 34.
[0120] Finally, the deposited material was annealed at 450°C for 4 hours, and the obtained composite silicon-carbon negative electrode material was recorded as (C / Si)@7TiO2 / TiN.
[0121] Comparative Example 1
[0122] The coconut shell porous carbon material was placed in a rotary kiln, and monosilane was introduced under nitrogen protection, with a monosilane gas flow rate: nitrogen flow rate = 1:9, and a deposition temperature of 400°C; after the silane deposition was completed, methane was introduced under nitrogen protection, with a methane flow rate: nitrogen flow rate = 1:9; Si: carbon skeleton = 1:1. After the deposition was completed, the furnace was cooled to obtain a silicon-carbon negative electrode material.
[0123] Comparative Example 2
[0124] The porous carbon material of waste cardboard is added into a rotary kiln, and monosilane is introduced under nitrogen protection, with the ratio of monosilane gas flow rate to nitrogen gas flow rate = 1:9, and the deposition temperature is 400°C; after the silane deposition is completed, methane is introduced under nitrogen protection, with the ratio of methane gas flow rate to nitrogen gas flow rate = 1:9; Si: carbon skeleton = 1:1. After the deposition is completed, the furnace is cooled to obtain a silicon-carbon negative electrode material.
[0125] The performance of the silicon-carbon negative electrode materials obtained in the examples and comparative examples was tested, and the results are shown in Table 1 below.
[0126] Table 1 Test results
[0127]
[0128]
[0129] From the above examples, it can be seen that the present invention provides a silicon-carbon composite negative electrode material with a surface-coated heterojunction structure and a preparation method thereof. From Table 1 above, it can be seen that when the deposition of titanium oxide / titanium nitride is 15 times and the deposition thickness is 30nm, the first efficiency and cycle performance of the material are greatly improved.
[0130] The present invention establishes a TiO2 / TiN heterojunction on the surface of silicon-carbon composite particles (such as Figure 2 As shown), a built-in electric field is formed to promote the transfer and separation of carriers at the contact interface, thereby improving the intrinsic ionic and electronic conductivity of the composite material. The capacity of the battery prepared by the negative electrode material coated with titanium oxide and titanium nitride structure of the present invention reaches 1900-2300mAh / g, the first efficiency reaches 90-95%, and the capacity retention rate is still as high as 92% after 100 cycles.
[0131] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A method for preparing a silicon-carbon composite negative electrode material with a surface-coated heterojunction structure, characterized in that: The following steps are involved: S1. A titanium oxide layer is coated on the surface of the silicon-carbon composite particles by atomic layer deposition to obtain silicon-carbon composite particles coated with titanium oxide layer; S2. A titanium nitride layer is coated on the surface of the silicon-carbon composite particles coated with the titanium oxide layer by atomic layer deposition; S3. Annealing the material deposited in step S2 to obtain a silicon-carbon composite negative electrode material with a surface-coated heterojunction structure.
2. The preparation method according to claim 1, characterized in that: In step S1 and step S2, the atomic layer deposition method includes the following steps: a. Load the reactant particles onto the reaction chamber carrier, evacuate the reaction chamber, and pass inert gas; b. Using an inert gas as a carrier gas, a reaction precursor is added into the reaction chamber in a pulsed manner for deposition; c. After the deposition is completed, the reaction chamber is evacuated by passing inert gas; d. Using an inert gas as a carrier gas, an oxidation precursor or a nitridation precursor is added into the reaction chamber in a pulsed manner to perform oxidation or nitridation treatment; e. Repeat steps b to d, with the number of cycles ≥ 1; The reactant particles are silicon-carbon composite particles or silicon-carbon composite particles coated with a titanium oxide layer.
3. The preparation method according to claim 2, characterized in that: In the step S1, in the atomic layer deposition method, the oxidation precursor includes one or more of water vapor, oxygen and ozone; In the step S2, in the atomic layer deposition method, the nitridation precursor includes ammonia and / or nitrogen.
4. The preparation method according to claim 2 or 3, characterized in that: In the step S1 and step S2, in the atomic layer deposition method, in the b, the reaction precursors independently include one or more of Ti(OC2H5)4, TiCl4, TiI4, TiCl4 and Ti(OCH(CH3)2)4.
5. The preparation method according to claim 2 or 3, characterized in that: In the step S1 and step S2, in the atomic layer deposition method, in the step b, the flow rate of the carrier gas is 15 to 25 sccm, and the residence time of the reaction precursor in the reaction chamber is 5 to 20 s.
6. The preparation method according to claim 5, characterized in that: In the step S1 and step S2, in the atomic layer deposition method, in the step b, the deposition temperature is 150-400° C., the pressure in the reaction chamber is 200-400 mTorr, and the pulse time is 300-800 ms.
7. The preparation method according to claim 2 or 6, characterized in that: In the step S1 and step S2, in the atomic layer deposition method, in the step d, the pulse time is 400 to 850 ms, the flow rate of the carrier gas is 15 to 25 sccm, and the residence time of the oxidation precursor or the nitridation precursor in the reaction chamber is 15 to 60 s.
8. The preparation method according to claim 7, characterized in that: The inert gas independently contains nitrogen and / or argon, and the temperature of the oxidation or nitridation treatment is 150-200° C.; The annealing temperature is 300-500° C., and the annealing time is 2-5 hours.
9. The preparation method according to claim 1 or 8, characterized in that: The thickness of the titanium oxide layer is 0.5-10 nm, and the thickness of the titanium nitride layer is 0.5-10 nm.
10. The silicon-carbon composite negative electrode material with a surface-coated heterojunction structure prepared by the preparation method according to any one of claims 1 to 9, characterized in that: It comprises silicon-carbon composite particles, a titanium oxide layer coated on the surface of the silicon-carbon composite particles, and a titanium nitride layer coated on the titanium oxide layer; The silicon-carbon composite particles have a C content of 10-90%, a Si content of 10-90%, and a particle size of 8-15 μm.
Citation Information
Patent Citations
Silicon-carbon composite negative electrode material and preparation method thereof
CN117457873A